Implementation of the Principles of Agreement (Contact) in Islamic Bank Fund Raising Products - Riska Jamal (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
The significant growth of Islamic Banks requires them to be able to meet the needs of the community by offering various products, one of which is a fundraising product that is in accordance with Sharia Principles. In order to raise funds, Islamic Banks provide various forms of financing that have their own contracts/agreements. This study aims to describe and analyze the principles of contracts in Islamic Bank fund raising products. The method used in this research is Library Research, with an analytical descriptive approach to clearly describe the principles of contracts in Islamic Bank fund raising products. The results showed that the principles of contracts in fund-raising products at Islamic Banks have been implemented properly, where the operational activities of Islamic Banks are carried out in accordance with sharia principles supervised by DSN-MUI. Islamic banks provide freedom to customers to choose the type of contract they want without coercion, and guarantee legal equality between the two parties in making the contract. In addition, every agreement made is written and binding, reflecting honesty and freedom in the preparation of contracts between Islamic Banks and customers. The implications of this study show that the implementation of good contract principles in Islamic Banks not only strengthens customer trust but also supports sharia compliance in banking operations. This is important for improving the sustainability and reputation of Islamic Banks in the midst of financial industry competition.